Integrative metabolomic and transcriptomic reveals potential mechanism for promotion of ginsenoside synthesis in Panax ginseng leaves under different light intensities - Di, Ping; Yang, Xiao; Wan, Mingming; Han, Mei; Zhang, Yonggang; Yang, Limin (Frontiers in Bioengineering and Biotechnology, 2023)
Panax ginseng C.A. Meyer is a shade plant, and its leaves are an important medicinal part of P. ginseng. Light intensity plays a crucial role in physiological activities and metabolite accumulation in P. ginseng. Currently, little is known about the molecular mechanisms underlying physiological changes and quality under different light intensities in P. ginseng leaves. Therefore, we investigated the changes in photosynthetic physiology, secondary metabolism, transcriptomics, and metabolomics of P. ginseng leaves under different light intensities [T20 (20 µmol• m -2 •s -1 ), T50 (50 µmol• m -2 •s -1 ), T100 (100 μmol•m -2 •s -1 )]T100 (100 µmol• m -2 •s -1 ]. Higher light intensity positively influenced the yield, photosynthesis, and accumulation of polysaccharides, soluble sugars, terpenoids, and ginsenosides in P. ginseng leaves. The T100 treatment notably promoted the accumulation of ginsenosides in the leaves, resulting in a 68.32% and 45.55% increase in total ginsenosides compared to the T20 and T50 treatments, respectively.